RNAi technology for management of banana bunchy top disease - Jekayinoluwa, T.; Tripathi, L.; Tripathi, J.N.; Ntui, V.O.; Obiero, G.; Muge, E.; Dale, J. (Wiley, 2020)
Banana bunchy top disease (BBTD) is one of the world's most destructive viral diseases of banana and plantain, causing up to 100% yield loss in severe cases. The disease is vectored by banana aphids (Pentalonia nigronervosa) and carried long distances through the movement of infected plant materials. The banana aphids harboring banana bunchy top virus (BBTV) present in banana producing regions are the sole vector and the most efficient method of transmitting the virus to the healthy plants. Controlling the spread of BBTD has been very challenging since no known banana germplasm is immune to BBTV. The disease can be managed with the use of virus‐free planting material and roguing. However, once BBTD is established in the field, it is very difficult to eradicate or manage it. Therefore, a more sustainable way of controlling the disease is developing host plant resistance against the virus and the vector. Biotechnological strategies via RNA interference (RNAi) could be used to target the banana aphid as well as BBTV to reduce virus‐associated yield losses of banana and plantain, which feed over 500 million people around the world. This review discusses the status of BBTD and perspectives on effective RNAi technologies for controlling BBTV and the vector, banana aphid, transmitting the virus as sustainable management of the disease.